Unbundling negative and positive externalities of nature in cities: The influence of wild animals on housing prices. (October 2019) - Broitman, Dani; Griskin, Vladimir; Czamanski, Daniel
Proximity to nature is highly valued by urbanites, who demonstrate higher willingness to pay for housing at locations near open and green spaces. However, nature in cities can generate negative externalities as well. In this article, we illustrate the complex relationship between cities and nature and suggest that their balance is time and location specific. The article presents estimates of positive and negative externalities based on data about encounters of humans with wild animals in the city of Haifa, Israel, and residential property values nearby. The data were analysed to uncover spatial regularities and basic statistical relationships. The results reveal the presence of dominant positive externalities when the human–wild animals interaction is low, driven by proximity to open and green areas. However, in certain areas and under certain circumstances, the nuisance generated by higher probabilities of encounters with wild animals near dwelling areas is correlated with lower property prices, overcoming the positive externalities of location near natural areas.